IS POLARIS LEAVING THE CEPHEID INSTABILITY STRIP? - Turner, D. G. (Одеські астрономічні публікації, 2017)
Although Polaris is generally regarded as an overtone pulsator that may soon switch to pulsation in the fundamental mode, it is argued that the variable is actually crossing the instability strip for the first time and is in the process of leaving the instability strip altogether. The luminosity of Polaris inferred from its optical F3 V companion, as well as from A, F, and G-type stars lying within a few degrees of it and populating a group main sequence coincident with that for Polaris B, is (MV) = -3.07±0.04 s.e., consistent with fundamental mode pulsation. The star's rate of period increase, 4.5 s yr-1, is also consistent with predictions from stellar evolutionary models for a fundamental mode pulsator crossing the instability strip for the first time, and its location redward of strip center agrees with similar predictions supporting a bluer instability strip for such stars. The onset of a much-reduced and irregular pulsation amplitude that began shortly after 1963-1966, when there was a glitch in the star's O-C data, suggests that the process of leaving the instability strip may have begun at that time. High quality photometric and radial velocity data for Polaris show no evidence for a second periodicity in its light signal that might indicate overtone pulsation. In summary, Polaris seems most likely to be a Cepheid that is crossing the instability strip for the first time and is now beginning the lengthy process of departing the instability strip altogether.